Prevalence and genetic divergence of Leptospira interrogans and Leptospira borgpetersenii in house rats (Rattus rattus) from Peninsular Malaysia - Mohamad Ikbal, Nurul Huda; Bhassu, Subha; Simarani, Khanom; Uni, Shigehiko; Chew, Chin Chan; Omar, Hasmahzaiti (Medknow Publications, 2019)
Objective: To evaluate the prevalence and divergence of genetically identified Leptospira spp. in the population of Rattus rattus. Methods: A total of 130 rats were used in this study. The infection within the rats were screened using polymerase chain reaction (PCR)-based diagnosis, with Leptospira genus-specific 16S rRNA primer and pathogenic Leptospira spp. specific LipL32 primer, on both kidney and liver tissues of Rattus rattus to detect the presence of potential Leptospira spp. Results: Out of 130 rats studied, 51 (39.23%) individuals were positive for leptospiral DNA. Basic Local Alignment Search Tool (BLAST) and phylogenetic analysis revealed that both pathogenic Leptospira interrogans and Leptospira borgpetersenii were predominantly identified. Phylogenetically, both genes disclosed similar clustering patterns of tree topologies between the two species. Although both genes were conserved, LipL32 gene portrayed higher nucleotide divergence (5.80%) compared to the 16S rRNA gene (0.60%). Minimum-spanning network displayed several haplotypes that are unique to each species, suggesting a higher degree of subdivision between both species. As for prevalence surveillance, both adult and subadult rats were susceptible to the infection, in which males were the most susceptible. Kidney was notable as the favourable organ for colonisation of leptospires. Rats captured from fresh markets were highly infected with Leptospira spp. (54.28%) compared to those from housing areas (26.47%). Conclusions: Rattus rattus represents an important asymptomatic transmitter of pathogenic leptospires, and hence is of public health concerns. © 2019 Asian Pacific Journal of Tropical Medicine Produced by Wolters Kluwer-Medknow. All rights reserved.